Understanding the concept of the Pi (π) number for pre-service teacher - Yus Mochamad Cholily; Beti Istanti Suwandayani (Institute of Advanced Engineering and Science, 2021)
This study examined the learning of Pi (π) numbers in elementary school mathematics. This research was conducted by employing case study method containing a single case concerning the Pi (π) numbers. A total of 432 pre-service teachers participated in the study from the academic year of 2019-2020. This research employed observation, interview, and document analysis as the data collection tool. The conduct of the research involving the teachers and pre-service teachers was made in the classroom environment. The practice that participants posed for the account of Pi (π) number were analyzed by descriptive analysis technique in the scope of qualitative analysis. The data obtained from the participants were summarized and interpreted according to the predefined theme, and findings were arranged by a direct citation of the problems. Based on the analysis of the research, it showed that participants had problems in determining Pi (π) numbers as Pi (π) numbers are only taught by memorization methods. The teachers also did not understand about the source of Pi (π) number. Learning Pi (π) numbers are directly practiced through problems and formulas. Understanding the formula of plane figures is also not yet understood, so teachers and students basically only memorize the formula.